A randomized trial of aprotinin (Trasylol) on blood loss, blood product requirement, and myocardial injury in total arterial grafting - Taggart, D; Djapardy, V; Naik, M; Davies, A (2003)
Background: Total arterial grafting is increasingly preferred in coronary artery bypass grafting, but it increases blood loss. Aprotinin (Trasylol; Bayer Corp, Leverkusen, Germany) reduces blood loss in cardiac surgery but has not been subjected to a randomized trial in total arterial grafting. Methods: A single-center, randomized, double blind, placebo-controlled trial of aprotinin administration in total arterial grafting was performed. The primary outcome variable was postoperative blood loss, and the secondary outcome variable was the number of units of donor blood or coagulant products transfused. The incidence of myocardial injury was determined from serial measurements of cardiac troponin T and creatine kinase-MB and renal injury from serum creatinine. Results: The placebo group (n = 34) and aprotinin group (n = 36) were similar with respect to all preoperative and intraoperative comparisons. One patient in each group underwent reexploration for bleeding. Open-label aprotinin was administered to 9 patients in the placebo group (26%) and to 2 patients in the aprotinin group (6%). There was a highly significant reduction in the median (interquartile range) blood loss in the aprotinin group compared with the placebo group (785 mL [590-1025 mL] vs 1525 mL [1175-1920 mL], respectively). Similarly, the aprotinin group demonstrated a marked reduction in the need for blood transfusion (77% vs 39%; P = .0001), the mean number of transfused blood units (2.6 vs 0.8, P < .001), and the number of patients requiring coagulant products (24% vs 3%; P < .001). There was no difference in myocardial injury in the 2 groups. Four patients in the aprotinin group had persistently elevated creatinine levels in the postoperative period (3 of whom had elevated preoperative creatinine levels and perioperative complications). Conclusions: Aprotinin significantly reduces blood loss and the need for blood component transfusion in patients undergoing total arterial grafting without increasing the risk of myocardial injury. Aprotinin should be considered routinely in patients undergoing total arterial grafting but cautiously in patients with an elevated preoperative creatinine level.